Development of New Biokinetic-Dosimetric Models for the Simulation of Iodine Blockade in the Case of Radioiodine Exposure in Man - Rump, Alexis; Eder, Stefan; Lamkowski, Andreas; Kinoshita, Manabu; Yamamoto, Tetsuo; Abend, Michael; Shinomiya, Nariyoshi; Port, Matthias (Drug Research, 2019)
In the case of nuclear incidents, radioiodine may be liberated. After incorporation it accumulates in the thyroid and by internal irradiation enhances the risk of cancer occurrence. By administering a large dose of non-radioactive iodine the uptake of radioiodine into the gland can be inhibited (“iodine blockade”). Biokinetic models using first order kinetics are not suited to simulate iodine blockade, as the uptake into the gland is mediated by a saturable active transport. Therefore, we integrated an uptake mechanism described by a Michaelis-Menten kinetic into a simple ICRP biokinetic model. We moreover added a total uptake blocking mechanism representing the Wolff-Chaikoff effect becoming active when the gland is saturated with iodine. The validity of the model was ascertained by comparison with IMBA software. The competition of radioiodine and stable iodine at the membrane carrier site was modeled according to the rate law for monomolecular reactions for competing substrates. Our simulations show that competition for the uptake at the membrane carrier site accounts for about 60% and the saturation of the gland with iodine for over 35% of the total protective efficacy that exceeds 95%. Following acute radioiodine exposure, it is preferable to administer a single large dose of stable iodine. In the case of continuous radioiodine exposure, a single dose of stable iodine is less effective than after an acute exposure and splitting the total available dose and shortening the dosage intervals enhance efficacy. Model-based simulations may be a useful tool to develop antidote dosage schemes for uncommon emergencies.
Keywords: Medical NRBC-protection; nuclear and radiological emergency; radioiodine; iodine blockade